Methods and tools for creating a mini server device using ESP32 (MMIT Proceedings, 2025)
This article explores the methods and tools for creating a mini server device using the ESP32 microcontroller. The ESP32 enables internet connectivity through its Wi-Fi and Bluetooth capabilities and can function effectively as a compact server. The paper describes key processes such as ESP32 programming, HTTP server development, and integration with sensors and actuators. This technology provides an efficient solution for remote control and monitoring over a network, demonstrating the ESP32’s potential in Internet of Things (IoT) applications